The Zakat Maal Management In The National Zakat Agency, Palembang City - Rijalus Sholihin (Institut Agama Islam Negeri (IAIN) Curup, 2020)
Purpose: The purpose of this study was to determine the management of Zakat Maal in the National Amil Zakat Agency (BAZNAS) of Palembang City and to determine the management of Zakat Maal l distribution in the National Amil Zakat Agency (BAZNAS) of Palembang City, and to find out the factors that are supporting and inhibiting the management of Zakat Maal in National Amil Zakat Agency (BAZNAS) in Palembang City. Design/Method/Approach: This type of research uses field research. Qualitative descriptive approach. Sources of data in this study are primary data and secondary data. Data collection techniques are observation, interview, and documentation. Data analysis techniques used in this study by descriptive methods such as data collection and then classified into data.Findings: The result of the research is that the management of Zakat mal l collection has just been socialized so that muzakki has not been too much even though the potential for muzakki is quite large. The absence of regulations related to the collection of Zakat maal to the public. The obstacles faced by the Palembang City National Amil Zakat Agency (BAZNAS) in the form of lack of human resources both in the field of collection and distribution and utilization, and less proactive and lack of transparency so that the interest of muzakki paying Zakat Maal at the National Amil Zakat (BAZNAS) of Palembang City is less interested in paying Zakat Maal l.Originality/Values: Provide information to the public on how to the management of Zakat Maal in the National Amil Zakat Agency (BAZNAS) of Palembang City